STUDI SOLIDIFIKASI POLIETERSULFON DALAM PELARUT N-METIL-2-PIRROLIDON DENGAN ADITIV POLYVINYL PYRROLIDONE DAN 2-(METHACRYLOYLOXY) ETHYL PHOSPHORYL CHLOLINE - Nasrul Arahman, Sri Aprilia, Teuku Maimun (Universitas Sumatera Utara, 2014)
In membrane preparation process via phase inversion method, the morphology of fabricated membranes are determined by composition and concentration of polymer, solvent, and non-solvent. The basic knowledge of the appropriate composition of those components are needed by cloud point experiment. In this work, the study on cloud point experiment have been done to investigate the solidification process of polymer system of polyethersulfone (PES) and 2-(methacryloyloxy) ethyl phosphoryl chloline (MPC) in N-methyl-2-pirrolidon (NMP) via phase inversion technique. Hydrofilik polymer MPC were used as a membrane modifying agent (MMA) in order to modify the surface property of fabricated membrane. In sum, addition of PVP and MPC into polymer solution brought about reducing amount of non-solvent necessary to obtain the cloud point of solution.